2019
DOI: 10.2147/jpr.s179061
|View full text |Cite
|
Sign up to set email alerts
|

Patients' return-to-work expectancy relates to their beliefs about their physician's opinion regarding return to work volition and ability

Abstract: PurposeThis study investigates the relationship between sick-listed patients’ return to work (RTW) expectancy and how they perceive that their physicians evaluate their ability and volition for RTW.MethodsHierarchical logistic regression controlling for sociodemographic factors and pain characteristics was carried out on cross-sectional data from 205 participants (mean age= 47.24±9.66 years, 83.9% women). They were currently on full-time sick leave with a total duration of 10 years or less and represented vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…We found an association between beliefs about returning to the same work within 6 months and RTW. Our finding is consistent with an earlier study among women on sick leave showing that a positive expectation/belief regarding RTW within a year was associated with the ability to work and volition that facilitated RTW [ 18 ]. In addition, negative recovery beliefs have been found to be a risk factor for NRTW (i.e., sustained long-term sick leave) among individuals with non-specific chronic MSP [ 60 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found an association between beliefs about returning to the same work within 6 months and RTW. Our finding is consistent with an earlier study among women on sick leave showing that a positive expectation/belief regarding RTW within a year was associated with the ability to work and volition that facilitated RTW [ 18 ]. In addition, negative recovery beliefs have been found to be a risk factor for NRTW (i.e., sustained long-term sick leave) among individuals with non-specific chronic MSP [ 60 ].…”
Section: Discussionsupporting
confidence: 93%
“…Several potential factors related to RTW among individuals with MSP have been studied previously. For example, psychological factors such as recovery beliefs, anxiety, depression, locus of control, and health-related quality of life have been shown to be associated with RTW among people with MSP [18][19][20][21]. Studies have also shown that RTW may be affected by painrelated behaviors such as pain intensity and fear-avoidance beliefs, and work-related factors such as job stress and job satisfaction [21,22].…”
Section: Introductionmentioning
confidence: 99%
“… 67 , 73 , 101 In a study of sick-listed individuals, Claréus et al (2019) demonstrated that positive (high) recovery expectations were significantly influenced by favourable beliefs about their physician's opinion regarding their ability and volition to return to work. 17 Conversely, physical therapists have described the difficulties relating to working with individuals who do not share their beliefs or attitudes towards pain and rehabilitation, particularly individuals with “passive” attitudes. 56 In this case, clinicians report finding working with these individuals demanding, because these patients, from their perspective, are more difficult to communicate with and empower.…”
Section: Discussionmentioning
confidence: 99%
“…Open access prominent determinant of return to work time, or other return to work outcomes, for musculoskeletal or mental health conditions. [27][28][29] The role of expectations on outcomes, including the expected and actual timing for return to work and driving after hand and wrist surgery, requires further exploration, particularly because expectations are a potentially modifiable characteristic which could be influenced by the advice provided by clinicians preoperatively.…”
Section: Discussionmentioning
confidence: 99%